PREPARATION OF MASTERS - FUTURE TEACHERS OF HIGHER EDUCATION FOR THE ORGANIZATION OF RESEARCH WORK OF STUDENTS - Yu.M. Kosenko (Academy of Cognitive and Natural Sciences, 2009)
The article is aimed to determine pedagogical conditions of intending high school teachers training for students' research work.